ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI PEMILIHAN KARIR DI STARTUP PADA GENERASI Z (STUDI KASUS PADA PT. XYZ) - Muhamad Ivan Akbar, Ivan (Fakultas Ekonomi dan Bisnis Universitas Satya Negara Indonesia, 2024)
Everyone dreams of achieving a successful and promising career. Therefore, this dream must be achieved with hard work. When a person's dream has been achieved, all the desires can be realized. Thus, everyone must have supporting qualities and focus on developing and improving their performance and responsibilities. For this reason, preparation is needed to face competition and challenges in an increasingly competitive world of work. The method is carried out using descriptive qualitative research methods. The data collection tool used was through in-depth interviews. Career Path shows that career path is a factor for Generation Z when choosing a career at a startup. They consider clear career prospects and opportunities for development to be significant. Work Environment shows that the work environment is a factor that influences generation Z's decision to choose a career at a startup. A flexible work environment is considered an essential factor for Generation Z. Work Culture shows that work culture is a factor for Generation Z in choosing a career at a startup. They look for a culture aligning with their values and a workplace supporting innovation and teamwork. Social Values show that social values are a factor in Generation Z's career choices in startups. Generation Z chooses companies whose social values align with their values, such as sustainability and social responsibility. Keywords: Career Path, Work Environment, Work Culture, and Values Social